Investigation on the mechanisms of carbapenem resistance among the non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae - Lee, Yee Qing; Sri La Sri Ponnampalavanar, Sasheela; Wong, Jia Haw; Kong, Zhi Xian; Ngoi, Soo Tein; Karunakaran, Rina; Lau, Min Yi; Abdul Jabar, Kartini; Teh, Cindy Shuan Ju (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundIn Malaysia, an increase in non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae (NC-CRKP) has been observed over the years. Previously, four NC-CRKP with increased susceptibility to ciprofloxacin in the presence of phenylalanine-arginine β-naphthylamide (PAβN) were identified. However, no contribution of the PAβN-inhibited efflux pump to carbapenem resistance was observed. All four NC-CRKP harboured non-carbapenemase β-lactamase, with two also exhibiting porin loss. In this study, we further investigated the genomic features and resistance mechanisms of these four isolates.MethodsAll four NC-CRKP were subjected to whole-genome sequencing, followed by comparative genomic and phylogenetic analyses.ResultsMulti-locus sequence typing (MLST) analysis divided the four NC-CRKP into different sequence types: ST392, ST45, ST14, and ST5947. Neither major nor rare carbapenemase genes were detected. Given the presence of non-carbapenemase β-lactamase in all isolates, we further investigated the potential mechanisms of resistance by identifying related chromosomal mutations. Deletion mutation was detected in the cation efflux system protein CusF. Insertion mutation was identified in the nickel/cobalt efflux protein RcnA. Missense mutation of ompK36 porin was detected in two isolates, while the loss of ompK36 porin was observed in another two isolates.ConclusionsThis study revealed that NC-CRKP may confer carbapenem resistance through a combination of non-carbapenemase β-lactamase and potential chromosomal mutations including missense mutation or loss of ompK36 porin and/or a frameshift missense mutation in efflux pump systems, such as cation efflux system protein CusF and nickel/cobalt efflux protein RcnA. Our findings highlighted the significance of implementing whole-genome sequencing into clinical practice to promote the surveillance of carbapenem resistance mechanisms among NC-CRKP.